2016
DOI: 10.1590/1982-0224-20150051
|View full text |Cite
|
Sign up to set email alerts
|

The brain of Brycon orbignyanus (Valenciennes, 1850) (Teleostei: Characiformes: Bryconidae): gross morphology and phylogenetic considerations

Abstract: The brain of Brycon orbignyanus is described as a model for future studies of the gross morphology of the central nervous system in Characiformes. The study of brain gross morphology of 48 distinct taxa of Characiformes, one of Cypriniformes, two of Siluriformes and two of Gymnotiformes, allowed us to propose, for the first time, six putative brain synapomorphies for the Characiformes and also two possibly unique gross brain morphology characters for the Siluriformes. A detailed protocol for the extraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The brain limits established herein for S. javae follow Pereira & Castro () with some modifications, i.e . the anterior portions of the bulbus olfactorius anteriorly, usually ending at the semi‐oval olfactory epithelium (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The brain limits established herein for S. javae follow Pereira & Castro () with some modifications, i.e . the anterior portions of the bulbus olfactorius anteriorly, usually ending at the semi‐oval olfactory epithelium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Abrahão & Shibatta () suggested that the corpus cerebelli is relatively large in all Pseudopimelodus Bleeker 1858 species when compared with species of Characiformes ( c.f . Pereira & Castro, ). In S. javae , the corpus cerebelli is very conspicuous and larger than in Pseudopimelodus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Datovo & Vari (), summarizing Wiley & Johnson (), revealed that within 180 major groups of Teleostei, 6% of synapomorphies are based on myology, 5% on splanchnology and 1% on neurology. Of the last, the first attempts to understand the neural‐complex date back to the beginning of the 20th century, but only from the mid‐1990s has neuroanatomy been used in systematic works on Antarctic fishes (Eastman & Lannoo, , , , , ) and more recently on Neotropical groups (Albert, ; Pupo, ; Abrahão & Shibatta, ; Pupo, ; Pereira & Castro, ). Likewise with other structures, such as the swimbladder capsule and Weberian apparatus, many studies were provided in the 19th century (Birindelli et al, ) and there has more recently been renewed interested in describing them (Birindelli et al, , ; Birindelli & Shibatta, ).…”
Section: Introductionmentioning
confidence: 99%